Comparison of Heart Rate Responses Between Coronary Heart Disease and Age‐Matched Normal Subjects in Water‐ and Land‐Based Exercise: A Pilot Study. Issue 2 (2017) - Graham, Scott M.; Baird, Marianne F.; Connaboy, Chris; Thow, Morag
Abstract : Background and purpose. : Exercise therapy is an integral component of cardiac rehabilitation (CR). Currently, land‐based exercise classes are prescribed in Phase IV CR. However, with its unique properties, water‐based exercise potentially offers an alternative, or additional mode of exercise, that could be utilized by rehabilitating individuals. The purpose of this pilot study was to measure and compare the heart rate (HR) response and perception of exercise intensity between similar land‐ and water‐based classes. Methods. : Participants in land‐based Phase IV CR classes (n = 7, aged 68 ± 7 yr) and similar aged‐matched participants partaking in water‐based exercise (n = 7, aged 64 ± 6 yr) completed 1‐hour exercise sessions on 4 consecutive weeks. HR in beats per minute (bpm) was measured continuously during each session, and rating of perceived exertion (RPE) (Borg scale 6‐20) was recorded at regular intervals. Results. : A main effect for HR was found (p < 0.05). During the 4 weeks, average HR in water was 9% higher than on land (water 85 ± 1 bpm vs. land 78 ± 5 bpm). Similar exercises elicited significantly higher HRs in water than on land (warm‐up 6% higher, shuttle run 9%, hamstring curls 17%, and cool‐down 8% in water compared to land) (p < 0.05). RPE was more accurately perceived in water, and, generally, RPE was lower in water. Discussion and conclusion. : The results of this study indicate that water‐based exercise allows individuals to maintain exercise workload at higher levels than similar exercise on land while perceiving variations in exercise intensity.